2012
DOI: 10.4314/ejesm.v4i4.10
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fallow Genealogical Cycles on the Build-up of Nutrients in Soils of the Cross River Rainforest, South-Southern Nigeria

Abstract: The study examined the effect of fallow generational cycles on the buildup of nutrients in the soil. Fallow sequence of 1 st , 2 nd , 3 rd , 4 th and 5 th generations were studied. The quadrat approach of sampling was employed to collect soil samples (surface and subsurface) from five plots of 10m x 10m across the five fallow generational cycles. Result showed that the mean proportions of organic matter (OM), total nitrogen (TN), cation exchange capacity (CEC) and available phosphorus (Av. P) increased substan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…The increase in the contents of OM and TN in the 2 nd year fallow is attributed to the increase in C. odorata cover. The increase in cover helps to reduce raindrop intensity and increases litter input which in situ decomposes to form nutrient (Aweto and Dikinya 2003;Offiong and Iwara, 2011). The OM and TN values obtained here also fall with the range of 1.83% and 0.35% in a similar study reported by Yahaya and Edicha (2010).…”
Section: Chemical Properties Of Soilssupporting
confidence: 88%
See 1 more Smart Citation
“…The increase in the contents of OM and TN in the 2 nd year fallow is attributed to the increase in C. odorata cover. The increase in cover helps to reduce raindrop intensity and increases litter input which in situ decomposes to form nutrient (Aweto and Dikinya 2003;Offiong and Iwara, 2011). The OM and TN values obtained here also fall with the range of 1.83% and 0.35% in a similar study reported by Yahaya and Edicha (2010).…”
Section: Chemical Properties Of Soilssupporting
confidence: 88%
“…Nevertheless, soil fertility continues to be a problem in many parts of the country as a result of the clearing and modification of forest mostly for agricultural production. The clearing of forest coupled with high temperature and precipitation accelerates soil erosion resulting in nutrient elements loss in dissolved and solid bound forms (Offiong and Iwara, 2011). However, after the cultivation of food crops, farmlands are deliberately allowed to fallow, a process for fertility restoration (Styger et al, 1999;.…”
Section: Introductionmentioning
confidence: 99%
“…The native P was more solubilized with organic acid and root exudates. Similarly, many authors found that soils under long term jhum fallow cycle contain more total N, P and Ca in the surface horizon (0-12 cm)" [27,36,37]. The significant increase in available P was observed from long jhum fallow cycle and statistically at par with undisturbed soil.…”
Section: Primary Nutrientsmentioning
confidence: 86%
“…The density of trees/shrubs provides adequate protection, releases root exudates to the soil thereby preventing unproductive nutrient losses. Similarly, many authors found that soils under long term fallow cycle contained more N, P and Ca in the surface horizon [27,41,36]. The exchangeable Ca and Mg as well as sulphur were held with colloidal clay particles thereby leading to their subsequent enhanced concentration in soil solution [42,43].…”
Section: The Correlation Between the Soil Properties Of The Jhum Soilmentioning
confidence: 99%
“…Pinho, unpublished data). In the near future, this can come to compromise soil fertility and other ecological and social characteristics of slash‐and‐burn systems in the studied communities (Fachin et al, 2021; Lawrence et al, 2010; Offiong & Iwara, 2012; Villa et al, 2018). In this sense, the implementation of highly diversified agroforestry systems, which follow the same growth processes as the natural succession of secondary forest (Cezar et al, 2015; Night & Diemont, 2013; Young, 2017), can indeed extend the time of use of slash‐and‐burn systems, without compromising their ecological and social functions, in addition to enhancing soil fertility (Chowdhury et al, 2020; Hands, 2021; Pinho et al, 2012).…”
Section: Discussionmentioning
confidence: 99%